Dealing with non-termination in DCGs - Vilares Ferro, M. (2001)
The objective of this paper is to study a practical approach to deal with non-termination in de nite clause grammars. We focus on two problems, loop and cyclic structure detection and representation, maintaining a tight balance between practical e ciency and operational completeness. In order to guarantee the validity of our conclusions, we rst map our study to a common situated framework, where the e ectiveness of each approach will be examined and, later, compared by running experiments.